The influence of perceived enjoyment, promotional urgency, and consumer trust on purchase decision of Whitelab via TikTok Live in Yogyakarta - Kartika Tifania Fadilla; Nina Fapari Arif (Jurnal STEI Ekonomi, 2025)
Live streaming commerce, an innovation in digital marketing that combines entertainment with live commerce, has emerged as a result of the development of social media. TikTok Live has become popular due to its ability to create an interactive, emotional, and real-time shopping experience. The purpose of this study is to investigate how perceived enjoyment, promotional urgency, and consumer trust affect consumers' decisions to purchase Whitelab skincare products promoted in Yogyakarta via TikTok Live. This study employs a quantitative approach, utilizing a survey method and a purposive non-probability sampling technique, with 150 respondents who have decided to purchase the product. The data were analyzed using PLS-SEM with SmartPLS 3.3.2 software. The results showed that the three independent variables had a positive and significant impact on purchase decisions. These findings suggest that enjoyment, promotional urgency, and trust in Whitelab sellers and their products are key factors influencing consumer decisions. This study contributes to the development of digital consumer behavior research and offers practical implications for live commerce-based promotional strategies that emphasize customer experience and trust-building.